64‐3: Patterned Glass Diffuser for MiniLED Count Reduction. Issue 1 (28th June 2022) - Mi, Xiang-Dong; Li, Donglei; Gao, Jie; Xu, Xiaofei; Sun, Haiwei; Jia, Lily; Han, Songfeng; Li, Chengshuai; Allen, Kirk R; Yi, Wei; Chen, Kaihui; Lamacchia, James F; et al.
Abstract : We report our progress on a monitor‐sized, dimensionally and thermally stable mini‐LED backlight enabled by a patterned glass diffuser (PGD). Our backlight uses 5, 000+ fewer mini‐LEDs per monitor — 4/9 times that in a reference mini‐LED backlight relying on a thicker diffuser plate, while it is thinner and achieves similar uniformity and luminance compared to the reference mini‐LED backlight.